Sobre el realismo convergente - León Olivé (Crítica)
This paper discusses Laudan´s claims (1981) that neither reference nor approximate truth explain the success of science as some realists have maintained; that the main realists theses about conceptual change and scientific progress are wanting, and that the history of science decisively confutes naturalistic scientific realist theses. Laudan´s arguments are examined in detail and it is shown that there are possible realist answers to his objections, provided a different view of scientific theories than the syntactic one normally accepted by naturalistic realists is assumed. This alternative view must include the notion of model as a central component of scientific theories, as developed e.g. by Harré (1970). It is also argued that Laudan´s arguments are based upon too narrow a conception of reference. It is shown that a more elaborated notion, e.g. that suggested by Kitcher (1978), can fruitfully be used by realists to explain convergence and also to rebut Laudan´s claim that there are theories, e.g. flogisto or ether theories, whose central terms did not refer but were nonetheless successful. The alternative view of reference sketched here according to Kitcher shows that some tokens of terms like ‘flogisto’ and ‘eter’ as used by the original flogisto and ether theorists did have genuine reference. The paper goes on to argue against the naturalistic idea that reference and approximate truth alone can explain why theories are accepted by scientists and why them follow, as a matter of fact, a retentionist methodology. Laudan shares the naturalistic idea that this is an empirical hypothesis, and so he tries to refute it on the basis of historical examples. The paper argues that this naturalistic view will not do. A broader theory of science is required which, besides realist theses, should develope adequate concepts to deal with the social factors of science; e.g. experimental practices, communication processes, exercises of power through them, etc. It is advocated that a theory of science of this type should be developed in order to defend realism. But then, most of the naturalistic premisses shared by realists and antirealists should be abandoned. An important consequence is that history of science, although not irrelevant for the realism-antirrealism debate, cannot be taken as a basis of neutral, hard facts, against which theories of science can founder. On the contrary, historical studies of science will necessary presuppose a theory of science. Therefore scientific realism must be seen as a philosophical doctrine to be disputed via philosophical arguments, and the idea that it is an empirical hypothesis should be abandoned. [L.O.]